Comparative Study on Financial Performance of Higher Education Legal Entities (PTN-BH) Before and During the Covid-19 Pandemic - Kusumadewi, Veronika Perwita; Yudianto, Ivan (Jurnal Pendidikan Akuntansi & Keuangan, 2024)
This study aims to determine the financial performance of Higher Education Legal Entities (PTN-BH) before and during the Covid-19 pandemic by using financial ratio assessments. The sampling technique was carried out using a purposive sampling method so that a total sample of 10 PTN-BH was obtained. The type of data used in this research is secondary data in the form of published financial report documents. The indicators for measuring financial performance consist of CR (Current Ratio), ROA (Return on Assets), ROE (Return on Equity), POBO (Operating Income to Operating Expenses) and FAT (Fixed Asset Turnover). Data analysis was performed using paired sample t test and Wilcoxon test. The results showed that there was no significant difference between PTN-BH before and during the Covid-19 pandemic in the ratios of ROA, ROE, POBO and FAT. While there are significant differences in the CR ratio.